The Moral Case to Pay Male Athletes More than Female Athletes - Block, Walter E. Block; W. McGee, Robert (Journal of Critical Realism in Socio-Economics (JOCRISE), 2024)
Professional female athletes have long and bitterly complained that their compensation seriously lags behind that awarded to their male counterparts, and that this situation is unjust. The problem with this argument is that it is based on the labor theory of value, a long-discredited theory that bases worth on inputs rather than outputs. The authors propose a market-based approach whereby male and female athletes are compensated based on what they add to the bottom line. The $24 million dollar lawsuit settlement awarded to the U.S. women’s national soccer (football) team on the basis of discrimination is analyzed from the perspective of economic theory and justice and found to be defective. The arguments used to obtain that settlement are being used in other sports and in other countries to obtain equal pay for women. If this defective line of reasoning is successful, the result will be to actually harm both men’s and women’s sports.